PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Atika Rahmah; Nur Jannah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to examine the use of AI in improving students' critical thinking skills in Islamic Education (PAI) learning at Yosowilangun State Senior High School 01. The method used in this study is a qualitative approach with a phenomenological design. Data were collected through observation and in-depth interviews with teachers and students, then analysed using data reduction, data presentation, and conclusion drawing techniques. The results of the study show that: First, AI-based learning has the potential to improve students' critical thinking skills if it is well supervised and directed. Second, AI can help support critical thinking skills to prepare students to become a generation that is critical in solving complex problems and is suitable for widespread application in Islamic Religious Education learning. Third, the implementation of AI can support students' thinking skills. With coordinated steps, students can respond to learning more actively, and teachers need to master how to process learning steps using AI so that students become more focused and their critical thinking skills do not weaken. The contribution of this study is to provide practical understanding for educators in utilising AI in this digital era to support the improvement of students' critical thinking.